A inimputabilidade como expediente literário: a guerra contra o homem em Um Sonho Americano de Norman Mailer - Lima, Olívia Maria Santos de (2014)
This dissertation aims to undertake a long journey through peculiar contexts in the historical spawn that goes from the post war of the XXth century until the explosion of the civil rights movement during the 60', having as scenery the United States of America. We have chosen to take this trip through the disturbing lengths of Norman Mailer, repeating his path in the novel An American Dream, central work of our research. We also aimed at detailing the issues that hunt the conscience of modern men, specially the State, composing beings who make mistakes and that are fully forgiven, ultimate argument of our analysis. We have tried thus understanding Norman Mailer writing through his characters, as well through the window of his arguments, which means a chaotic world that is far from being understood.